DINAMIKA HARGA DAN PERDAGANGAN KOMODITAS JAGUNG - RACHMAN, BENNY (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Corn price in Indonesia is quite related to corn price in the world market, exchange rate, and trade policy. These aspects give some impact on domestic price stabilization policy. In line with those issues, the objectives of this study are: (1) to analyze domestic and international corn price prospective, (2) trade situation of corn commodity, and (3) to asses price transmission elasticity. Results of this study reply that corn price in the international market tend to decrease gradually. Growth of domestic corn price is affected by international economic condition i.e. international price and exchange rate. This case indicated by perfectly price transmission. Furthermore, to anticipate lower corn price in the international market and to support domestic producers, government should have implemented import tariff periodically. In addition to support price policy, government should also consider the improvement institutional aspects, such as marketing structure, farmers’ empowerment, and price stabilization.
Keywords: Liberalization, Price Transmission, Price Policy